First record of the Mediterranean mussel Mytilus galloprovincialis (Bivalvia, Mytilidae) in Brazil - Belz, Carlos Eduardo (2020)
The genus Mytilus comprises a large number of bivalve mollusk species distributed throughout the world and many of these species are considered invasive. In South America, many introductions of species of this genus have already taken place, including reports of hybridization between them. Now, the occurrence of the Mediterranean mussel Mytilus galloprovincialis is reported for the first time from the Brazilian coast. Several specimens of this mytilid were found in a shellfish growing areas in Florianópolis and Palhoça, Santa Catarina State, Brazil. Morphological analysis of the shells and molecular analysis through sequencing of the cytochrome oxidase subunit 1 (COI) confirmed the taxonomic identification. The species is known for its great invasive potential and can become a major environmental problem for seafood business and coastal communities, as it can compete and even hybridize with local species.